Mahākavi "Hariaudha" kā "Priya-pravāsa" - Śāstrī, Dharmendra Brahmacārī (SAMP early 20th-century Indian books project ;, 1944)
Study of Priyapravāsa, poem by Ayodhyāsiṃha Upādhyāya, 1865-1947, Hindi author.